Stamp your stuff - McGraw, MaryJo, 1961- (Cincinnati, Ohio : North Light Books, 2004)
Provides instructions for using stamps, paints, and other materials to decorate everyday objects and show off one's personal style.
5.2
3-6
Keywords: Rubber stamp printing -- Juvenile literature; Rubber stamp printing; Handicraft